Multiple quantum products in toric varieties - Holger Spielberg (International Journal of Mathematics and Mathematical Sciences)
We generalize the author's formula for Gromov-Witten invariants of symplectic toric manifolds (1999) to those needed to compute the quantum product of more than two classes directly, that is, involving the pullback of the Poincaré dual of the point class in the Deligne-Mumford spaces ℳ¯0,m.